Diagnostic value of miR-637 in patients with atherosclerosis and its predictive significance for the future cardiovascular events. (October 2021) - Xu, Yuxia; Zhao, Lixiang; Liu, Hai; Sun, Bin; Zhao, Xinxiang
Objectives: Atherosclerosis is a common vascular disease. MiR-637 has been demonstrated to be low-expressed in hypertensive patients, and atherosclerosis is closely related to hypertension. Therefore, this study speculated that miR-637 may play an important role in the development of atherosclerosis. In brief, this study examined the expression level of miR-637 in patients with atherosclerosis and further analyzed its clinical value in patients with atherosclerosis. Methods: The expression level of miR-637 was detected in serum from 86 patients with atherosclerosis and 75 healthy controls by using quantitative reverse transcription-polymerase chain reaction. The receiver operating characteristic curve was used to assess the diagnostic value of miR-637 in atherosclerosis. Pearson's correlation analysis was performed to evaluate the relationship between serum miR-637 and different clinical parameters. The prognostic value of miR-637 in atherosclerosis was analyzed by the Kaplan–Meier survival curve and multivariate cox regression analysis. Results: Compared with healthy individuals, miR-637 was downregulated in the serum of atherosclerosis patients. The receiver operating characteristic curve suggested the high diagnostic value of miR-637 for atherosclerosis, with the AUC of 0.853, specificity of 77.9%, and sensitivity of 80.0%. The expression level of miR-637 was negatively correlated with CIMT (r = –0.8101, P  <   0.0001) and CRP (r = –0.6154, P  <   0.0001), respectively. Survival analysis indicated that miR-637 was also found to be an independent prognostic factor for atherosclerosis. Conclusions: MiR-637 is a potential noninvasive diagnostic marker of atherosclerosis and has important predictive value for the occurrence of future cardiovascular events.